2007
DOI: 10.1038/sj.bjc.6603986
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study investigating the role of lymphadenectomy, surgical castration and adjuvant hormonal treatment in endometrial stromal sarcoma

Abstract: The objective of this study is to assess the therapeutic importance of surgical castration, adjuvant hormonal treatment and lymphadenectomy in endometrial stromal sarcoma (ESS). A retrospective and multicentric search was performed. Clinicopathologic data were retrieved from cases that were confirmed to be ESS after central pathology review. The protocol was approved by the Ethical Committee. ESS was confirmed histopathologically in 34 women, but follow-up data were available in only 31 women. Surgical treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
74
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(79 citation statements)
references
References 28 publications
2
74
0
3
Order By: Relevance
“…Similarly, Li et al (2005) found that ovarian preservation did not affect recurrence or survival in women with stage I low-grade ESS. Similar findings were described by Amant et al (2007) in a multicenter analysis of 34 women with ESS. In stage I -II premenopausal women who underwent hysterectomy with or without bilateral saplingo oophorectomy, 3 of 12 (25%) and 1 of 6 (17%) recurred, respectively.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Similarly, Li et al (2005) found that ovarian preservation did not affect recurrence or survival in women with stage I low-grade ESS. Similar findings were described by Amant et al (2007) in a multicenter analysis of 34 women with ESS. In stage I -II premenopausal women who underwent hysterectomy with or without bilateral saplingo oophorectomy, 3 of 12 (25%) and 1 of 6 (17%) recurred, respectively.…”
Section: Discussionsupporting
confidence: 76%
“…The standard surgical procedure has included a total abdominal hysterectomy, bilateral salpingo-oophorectomy, and radical cytoreductive surgery of extra-uterine disease (Gadducci et al, 1996). Moreover, despite traditional recommendations to include bilateral salpingooophorectomy in the primary surgical management of ESS, some investigators have advocated preserving ovarian function, particularly in younger women (Gadducci et al, 1996;Chu et al, 2003;Li et al, 2005;Amant et al, 2007). The role of pelvic and para-aortic lymphadenectomy, and adjuvant therapy with radiation therapy, chemotherapy, or hormonal treatment remains controversial.…”
mentioning
confidence: 99%
“…The problem with regard to earlier studies is that the various conditions were aggregated, preventing meaningful analysis of any single variable (6)(7)(8)(9)(10)(11)(12)(13). Further, some recent studies are still using the older classification (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) …”
Section: Discussionmentioning
confidence: 99%
“…7,9 Standardized treatments for uterine sarcomas have not been established, and treatments differ according to the histological subtype. [7][8][9][10] Because of these diagnostic, prognostic, and therapeutic differences, magnetic resonance (MR) imaging becomes an important tool for the initial diagnosis of uterine sarcoma. Several studies have presented MR findings of uterine sarcoma, but diagnosing and distinguishing specific sarcoma groups have been difficult because of the variability of their malignant components, including hemorrhage and necrosis.…”
Section: Introductionmentioning
confidence: 99%